2020
DOI: 10.1108/jbim-12-2019-0504
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management, customer relationship management and innovation capabilities

Abstract: Purpose The purpose of this study is to introduce a unified framework, which integrates knowledge management (KM) (knowledge acquisition, diffusion and application, knowledge from a customer, knowledge about customers and knowledge for customers), customer relationship management (CRM) success (information sharing, customer involvement, long-term partnership, joint-problem solving and technology-based CRM) and innovation capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 94 publications
1
75
0
8
Order By: Relevance
“…Furthermore, Jie et al (2013) confirmed the existence of a strong relationship between supply chain practices and competitive advantage. Finally, recent studies have emphasised that SCM practices such as buyer-supplier relationships (Afraz et al, 2021), information sharing (Huo et al, 2021) and customer relationship management (Migdadi, 2021) influence different facets of competitive advantage. This leads to the hypothesis that: H1.…”
Section: Supply Chain Management (Scm) Practices and Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jie et al (2013) confirmed the existence of a strong relationship between supply chain practices and competitive advantage. Finally, recent studies have emphasised that SCM practices such as buyer-supplier relationships (Afraz et al, 2021), information sharing (Huo et al, 2021) and customer relationship management (Migdadi, 2021) influence different facets of competitive advantage. This leads to the hypothesis that: H1.…”
Section: Supply Chain Management (Scm) Practices and Competitive Advantagementioning
confidence: 99%
“…Logistics integration is also positively related to competitive advantage in the form of dimensions such as quality, delivery flexibility and cost (Prajogo and Olhager, 2012;Chinomona and Pooe, 2013). In addition, SCM practices are also positively related to competitive advantage (Jie et al, 2013;Afraz et al, 2021;Huo et al, 2021;Migdadi, 2021). For example, Mellat-Parast and Spillan (2014) found that supply chain strategies influence logistics integration, which in turn significantly influences firms' competitive positions.…”
Section: H5 Logistics Integration Positively Affects Competitive Advantage In Smesmentioning
confidence: 99%
“…Para Migdadi (2020), la consolidación del capital estructural en una organización en uno de los requisitos esenciales para alcanzar los objetivos en una organización de conocimiento, y de manera particular, para lograr la sostenibilidad y escalabilidad de estos ejercicios. Lo anterior reviste especial importancia dado que, las prácticas de gestión de conocimiento posibilitan la gestión de los intangibles en la organización y permiten logros significativos en términos de metas empresariales, pero lo más importante, es que este tipo de prácticas se instalen en la organización como parte de su cultura y sean incorporadas de manera sistemática y permanente a fin de generar circulos virtuosos que desemboquen en una organización competitiva, con mayores posibilidades de crecimiento y con una alineación entre las perspectivas individuales y los objetivos propuestos en la visión organizacional (Ali et al, 2017).…”
Section: Discussionunclassified
“…With the advent of the era of knowledge economy, knowledge is regarded as an important resource of organizations, and many organizations realize that knowledge management is an important way to achieve sustainable competitive advantage [9,10]. Knowledge management is the activity of planning and managing the creation and application of knowledge [11]. Knowledge sharing is an important link of knowledge management [12], and it is the activity transferring knowledge from one person or organization to another [13].…”
Section: Introductionmentioning
confidence: 99%